P-182 Working collaboratively to improve end of life care training in south london. Issue Volume 5: Issue (2015)Supplement 3 (1st November 2015) - Heaps, Kate; Bryan, Liz; Berg, Jane; Perna-Forrest, Letizia; Linehan, Gail; Menezes, Toni; Wilcocks, Tricia; Vandeweghe, Maaike; Shaw, Nicky; Moback, Berit
Abstract : Background: In response to the need for training highlighted in the Neuberger and Staffordshire reports in 2013 the eight adult and children's hospices in South London have formed a Collaborative to plan, develop and evaluate training. The collaborative approach is an example of Hospice UK vision of Hospice Consortium for Education. SLHEC works closely with Health Education South London (HESL). Aims: Utilise knowledge, expertise and education and training resources efficiently Ensure training is accredited and transferrable Submit joint proposals for funding Influence the implementation of the HESL End of Life Care Education and Training Strategy (2015) Liaise with CEPNs (Community Education Provider Networks) and other Strategic Networks Explore new opportunities in the education market Education Leads and CEs meet bi-monthly to discuss strategic developments. The Collaborative is chaired by one of the CEs and supported by a project manager. Achievements and challenges: Delivering five HESL funded training programmes QELCA – Five day course of experiential learning combining clinical, theoretical and action planning. Volunteer Training – Standardised model for volunteers in patient/client facing roles Level 5 Diploma – Apprenticeship – Assistant Practitioner (Band 4) – City and Guilds 2 year apprenticeship course for HCA, delivered in collaboration between hospices, care home and Croydon College (FEI) Level 3 Diploma in Health and Social Care–Apprenticeship – QCF course with bolt on module on LTC and frailty, delivered in collaboration with Croydon College (FEI) National Care Certificate – Accredited training delivered tocare home Links with HEI/FEI/NHS Trusts/CEPNs. CPPD funding to hospice staff. Challenges include managing the different priorities and capacities of individual hospices, employers unable to release staff and short term funding. Plans: Robust evaluations Ensure sustainability Increasing educational capacity Disseminatelearningto Hospice UK/stakeholders Workforce Planning